2000
DOI: 10.1007/s11738-000-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth regulators on tomato (Lycopersicon esculentum) fertility

Abstract: The aim of the study was to determine the effect of 2,4 D (2,4di-chlorophenoxyacetic acid) used separately and in a mixture with BAP (benzylaminopurine) on fertility and some features of tomato fruit. The plant flowers were immersed only once in water solutions of the growth regulators (2,4 D 0.001%; 0.005 %; 2,4 D 0.001% + BAP 0.001%; 2,4 D 0.005 % + BAP 0.005 %). The mean fruit weight, fruit volume, specific weight, and the jelly weight were determined. The number of seeds collected from the fruit was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…It is a well-known fact that seeds play an important role in regulating fruit growth and development. According to the report of Nowaczyk and Nowaczyk (2000) treating tomato flowers with PGRs resulted in setting the fruits with smaller number of seeds or in extreme cases, in setting seedless fruits which coincide with the findings of this study especially when 2,4-D sprayed at 5 and 10 ppm. Bradford et al (2003) indicated that regulation of LeSNF4 expression by ABA and GA provides a potential link between hormonal and sugar-sensing pathways controlling seed development, dormancy, and germination.…”
Section: Effect On Seed Number and Weight Per Fruit And Fruit Sizesupporting
confidence: 89%
See 1 more Smart Citation
“…It is a well-known fact that seeds play an important role in regulating fruit growth and development. According to the report of Nowaczyk and Nowaczyk (2000) treating tomato flowers with PGRs resulted in setting the fruits with smaller number of seeds or in extreme cases, in setting seedless fruits which coincide with the findings of this study especially when 2,4-D sprayed at 5 and 10 ppm. Bradford et al (2003) indicated that regulation of LeSNF4 expression by ABA and GA provides a potential link between hormonal and sugar-sensing pathways controlling seed development, dormancy, and germination.…”
Section: Effect On Seed Number and Weight Per Fruit And Fruit Sizesupporting
confidence: 89%
“…The authors reported an increase in fruit weight due to 2,4-D application which could be also due to stimulation of parthenocarpic fruit growth by PGR that resulted in increased fruit weight. Nowaczyk and Nowaczyk (2000) reported that decrease in number of seed in fruits accompanied by production of smaller amount of jelly surrounding the seeds which may affect juice volume for processing tomato. However, under this experiment either 2,4D or GA 3 in single or combined application resulted in significant variation in fruit juice volume (data not present) as compared to the control treatment but it improved fruit pericarp thickness which may contribute to juice volume, TSS (Brix) and TA (%) (Dandena et al, 2010).…”
Section: Effect On Seed Number and Weight Per Fruit And Fruit Sizementioning
confidence: 99%